2022
DOI: 10.3390/cancers14153783
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immunohistochemistry Markers in Endometrial Cancer with Mismatch Repair Deficiency: A Systematic Review

Abstract: The objective of this systematic review was to summarize our current knowledge of the role of immunohistochemistry (IHC) markers for identifying mismatch repair-deficient (MMRd) tumors in endometrial cancer (EC). Identification of MMRd tumors, which occur in 13% to 30% of all ECs, has become critical for patients with colorectal and endometrial cancer for therapeutic management, clinical decision making, and prognosis. This review was conducted by two authors applying the Preferred Reporting Items for Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 180 publications
1
23
1
2
Order By: Relevance
“…Previous studies found that combined PD-L1 positivity and MMR deficiency was associated with adverse findings, such as high tumour grade [10] ; therefore, there is a potential role for immunotherapy to benefit EC patients with MMR deficiency [6] , [7] , [9] , [12] . The association found between PD-L1 positivity and MMR deficiency in the present study was lower than reported previously [28] . This could be attributed to sampling and TMA matters.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies found that combined PD-L1 positivity and MMR deficiency was associated with adverse findings, such as high tumour grade [10] ; therefore, there is a potential role for immunotherapy to benefit EC patients with MMR deficiency [6] , [7] , [9] , [12] . The association found between PD-L1 positivity and MMR deficiency in the present study was lower than reported previously [28] . This could be attributed to sampling and TMA matters.…”
Section: Discussioncontrasting
confidence: 93%
“… 10 Most commonly, MSI-H endometrial cancer is associated with the methylation of MLH1 promoter. 11 , 12 MSI-H endometrial cancers are characterized by lower stage and intermediate prognosis. 13 , 14 In the Le et al study, endometrial cancer represented the second most common malignancy with MMR deficiency, accounting for 17% of the enrolled patients ( N = 15).…”
Section: Preliminary Clinical Data and Published Resultsmentioning
confidence: 99%
“…G enomic and transcriptomic analyses of endometrial carcinoma (EC) have shown that 25% to 30% of tumors harbor a high frequency of somatic mutations that are attributable to deficiencies of DNA mismatch repair (dMMR), resulting in chromosomal changes referred to as microsatellite instability high (MSI-H). 1 This alteration of chromosomal biology and the resulting high mutation rate are thought to increase the expression of tumor-associated neoantigens, making MSI-H tumors logical targets for immunotherapy. In 2017, pembrolizumab as a single agent received accelerated approval by the US Food and Drug Administration (FDA) for treatment of refractory dMMR/MSI-H solid tumors, including EC.…”
mentioning
confidence: 99%
“…[4][5][6] In 2019, the European Society for Medical Oncology (ESMO) consensus recommendations indicated immunohistochemistry (IHC) as the first test of choice for the 4 key MMR proteins and molecular analysis of the dMMR phenotype for mandatory confirmation if MMR immunohistochemical analysis (MMR-IHC) yielded a doubtful result. 1 Then, in 2022, the FDA approved a label expansion for the Ventana MMR RxDx Panel as the first IHC companion diagnostic test to help identify patients with dMMR solid tumors who may be eligible for immune checkpoint blockade monotherapy with pembrolizumab. The panel is also the first companion diagnostic test to help identify patients with EC whose tumors show proficient MMR (pMMR), and who may be eligible for combination therapy with pembrolizumab and the tyrosine kinase inhibitor lenvatinib.…”
mentioning
confidence: 99%
See 1 more Smart Citation